Peran Orang Tua dalam Mendidik Anak di Rumah: Sosialisasi Pembentukan Nilai dan Karakter di TK-KB Al-Hijrah Kota Jambi - Winda sherly utami; Indryani; Sri Indriani Harianja; Agnes Purba; khalisah, Nur; Rozanah (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This outreach activity aims to increase parents' understanding of character education in early childhood and provide practical guidance for implementing it at home. The activity was carried out in one of the kindergartens involving 16 parent participants. Implementation methods include planning, implementation and evaluation stages. At the planning stage, parents' needs are identified and relevant materials are prepared. The activities include presentation of material, experience sharing sessions, and question and answer sessions, which take place interactively and emotionally, providing space for parents to share challenges and solutions in educating children. The results of the activity show that parents face various difficulties, such as dividing their time between work and accompanying their children, but this activity provides new insights and emotional support which the participants feel is useful. Evaluation through questionnaires shows an increase in parents' understanding of the importance of character education at home. It is hoped that this activity can be the first step in building synergy between parents and educational institutions to support children's optimal growth and development.